Creating An Educational Science Website Leveraging Beach Edutourism to Enhance Scientific Literacy - Wulandari, Ana Yuniasti Retno; Putera, Dwi Bagus Rendy Astid; Sutarja, Maria Chandra (Jurnal Inovasi Pendidikan IPA, 2025)
Connecting lessons to students' surroundings makes it easier for them to understand and use science skills. This research aimed to create a practical science website about Talang Siring Beach edutourism to help students practice these skills. The science website media was developed using the ADDIE model. A post-test-only control group design was used for the implementation stage of the research design. The research subjects were 59 students who were split into two classes (31 students in the experimental class and 28 students in the control class). The instruments used included a validation questionnaire for the feasibility of media and material aspects, a response and readability questionnaire, and also a science literacy test. The Mann-Whitney U test was used to compare the experimental and control classes' scientific literacy levels. The results of this study show the developed media is valid (0.89 for the feasibility aspect and 0.9 for material feasibility). The response to and readability of the website media are in a good category. The results of the Mann-Whitney U test show a difference in scientific literacy skills between the two classes (sig. 0.000 < 0.05). The experimental class has a higher level of scientific literacy than the control class. The study found that the Talang Siring Beach science website works well and boosts students' scientific literacy. This means teachers should link learning to the local environment so students can better solve problems around them. Future work should pair these websites with effective teaching strategies.